Synthesis, Molecular Docking, and Antimalarial Activity of Hybrid 4-Aminoquinoline-pyrano[2,3-c]pyrazole Derivatives - Mohd Asyraf Shamsuddin; Amatul Hamizah Ali; Nur Hanis Zakaria; Mohd Fazli Mohammat; Ahmad Sazali Hamzah; Zurina Shaameri; Kok Wai Lam; Wun Fui Mark-Lee; Hani Kartini Agustar; Mohd Ridzuan Mohd Abd Razak; Jalifah Latip; Nurul Izzaty Hassan (MDPI AG, 2021)
Widespread resistance of Plasmodium falciparum to current artemisinin-based combination therapies necessitate the discovery of new medicines. Pharmacophoric hybridization has become an alternative for drug resistance that lowers the risk of drug-drug adverse interactions. In this study, we synthesized a new series of hybrids by covalently linking the scaffolds of pyrano[2,3-c]pyrazole with 4-aminoquinoline via an ethyl linker. All synthesized hybrid molecules were evaluated through in vitro screenings against chloroquine-resistant (K1) and -sensitive (3D7) P. falciparum strains, respectively. Data from in vitro assessments showed that hybrid 4b displayed significant antiplasmodial activities against the 3D7 strain (EC50 = 0.0130 ± 0.0002 μM) and the K1 strain (EC50 = 0.02 ± 0.01 μM), with low cytotoxic effect against Vero mammalian cells. The high selectivity index value on the 3D7 strain (SI > 1000) and the K1 strain (SI > 800) and the low resistance index value from compound 4b suggested that the pharmacological effects of this compound were due to selective inhibition on the 3D7 and K1 strains. Molecular docking analysis also showed that 4b recorded the highest binding energy on P. falciparum lactate dehydrogenase. Thus, P. falciparum lactate dehydrogenase is considered a potential molecular target for the synthesized compound.